التحكيم في منازعات عقود البناء والتشغيل ونقل الملكية في القانونين العماني والمصري : دراسة تحليلية مقارنة - علوي، هلال بن محمد بن سليمان (Ahmad Ibrahim Kulliyyah of Law, International Islamic University Malaysia, 2016)
This study aims to discuss the issue of arbitration in disputes relating to build, operate and transfer contracts in the light of the Omani Arbitration Law which are then compared to the Egyptian Arbitration Law. It starts from an important problematic task which is to what extent it is possible to accommodate the rules of Omani Arbitration Law and relate Omani legislation rules to all matters that arbitrate the disputes of build, operate and transfer contracts as well as the extent of availability of control on the legality of recourse to arbitration in disputes such as contracts which the state or one of its branches is a party. The researcher concludes that the Omani law has authorized arbitration in disputes of these contracts. It also means that the texts organize the arbitration process in all its various stages, but the legal texts contained therein do not have any control or procedural restriction allow the administrative authority to resort to arbitration to settle disputes arising from these contracts, which allow the administrative authority agreement with the contracted party to resort to arbitration without being subject to any restrictions. Procedural in this regard has given importance and seriousness to this type of contract on the country's economy, national security and natural wealth. The researcher insists on the need to pass a separate legislation which regulates the arbitration process arising from disputes of build, operate, and transfer contracts. Also it has recourse to the arbitration in the disputes these contracts restrictive came with the consent of the Council of Ministers upon the proposal of the competent minister, with inadmissibility of the mandate in this matter. As this case requires the pledge of administrative contracting specialists of legal professionals, the task is in the formulating condition of arbitration when inserted in build, operate and transfer contracts. Also it requires the application of the national law on conflicts that may arise from these contracts.